ANALISIS SISA UMUR PAKAI TPA REGIONAL BANJARBAKULA TANPA DITERAPKANNYA UPAYA PEMILAHAN SAMPAH RESIDU - Maylana, Fitria Rizky; Mahyudin, Idiannoor; Hafizianor, Hafizianor; Febrianty, Irma (EnviroScienteae, 2024)
Evaluation indicates that the institutional framework of the Banjarbakula Regional Landfill (TPA) requires improvement, particularly in terms of structural positions and human resource expertise. This research aims to analyze the remaining operational life of the Banjarbakula Regional Landfill without the implementation of residual waste separation efforts. The study was conducted at the Banjarbakula Regional Landfill, located on Jalan Gunung Kupang, Cempaka District, Banjarbaru City. The analysis of the landfill's remaining life employs a quantitative descriptive method, analyzing data on the volume of waste entering the landfill from 2019 to 2023 and the available land area for waste deposition. This projection of waste accumulation is derived from direct observations, measuring the remaining land capacity for waste, and assessing the landfill's total capacity. Based on this analysis, an evaluation of the landfill's remaining operational life can be performed. Without the implementation of residual waste separation, the Banjarbakula Regional Landfill is projected to reach its full capacity in 3 years and 6 months, specifically by September 2028, indicating a suboptimal performance at the Banjarbakula Regional Landfill.